Multiple rib fractures: does flail chest matter?. Issue 7 (13th May 2021) - Daskal, Yaakov; Paran, Maya; Korin, Alexander; Soukhovolsky, Vladislav; Kessel, Boris
Abstract : Background: Recent studies have reported significant morbidity and mortality in patients with multiple rib fractures, even without flail chest. The aim of this study was to compare the clinical outcome and incidence of associated chest injuries between patients with and without flail chest, with three or more rib fractures. Methods: This study included patients with blunt trauma with at least three rib fractures, hospitalised during 2010–2019 in the Hillel Yaffe Medical Center in central Israel (level II trauma centre). Patients with and without radiologically defined flail chest were compared with regard to demographics, Injury Severity Score (ISS), GCS, systolic blood pressure (SBP) on admission, radiological evidence of flail chest, associated chest injuries, length of stay in intensive care unit, length of hospitalisation and mortality. Results: The study included 407 patients, of which 79 (19.4%) had flail chest. Overall, pneumothorax and haemothorax were more common among patients with flail chest (p<0.05). When comparing patients with three to five rib fractures, there was no difference in length of intensive care and length of hospitalisation or mortality; however, there was a higher incidence of pneumothorax (24.6% vs 50.0%, p<0.05). When comparing patients with six or more rib fractures, no difference was found between patients with and without flail chest. Conclusion: In patients with three to five rib fractures, pneumothorax is more common among patients with flail chest. Clinical significance of flail chest in patients with more than six rib fractures is questionable and flail chest may not be a reliable marker for severity of chest injury in patients with more than six fractures.